Penggunaan Tracer Berkas Rekam Medis di Klinik Laras Hati - Tri Ariani; Nanda Surya Febrianta (Universitas Gorontalo, 2022)
Primary Clinic is a health service facility that provides individual health with basic medical services. Regulation of the Indonesian Ministry of Health No. 028 in 2011 concerning clinics, stated it providing services is required to maintain medical records. According to the Director General of Medical Records, the quality of medical record storage in 2006 by sorting to prevent misfiles and using tracer as guidance for storing or returning medical records that come out of storage shelves. Misfile medical records can be minimized with tracers. Tracer is available at Laras Hati Clinic but has never been evaluated for use. This study to know use of tracers in medical record files and problems of using them at Laras Hati Clinic. Type of research is a qualitative descriptive study with content analysis approach. Data collection techniques used in-depth interviews, observation, and documentation studies. Sample in this study consisted of midwives, nurses, registration officers, and medical record unit officers at the Laras Hati Clinic who were defined by inclusion criteria and exclusion criteria. Storage of medical records with a centralized system, the number used is medical record number. Alignment system with SNF (Straight Numbering Filing) system. There are medical records placed in cardboard boxes on the floor, therefore officers have difficulty finding medical record documents, due to lack of storage shelves, use of tracers isn’t optimal because not all officers use tracers in taking medical records, tracers have not been filled in, number of tracers is limited, while patients who visited exceed the availability of tracer. The control card on the tracer isn’t filled, therefore it isn’t possible to track the purpose of medical record file, there is no SOP for using the tracer. Keywords; use; tracer; medical records Abstrak Klinik Pratama adalah fasilitas pelayanan kesehatan yang menyelenggarakan pelayanan kesehatan perorangan yang menyediakan pelayanan medis dasar. Menurut Permenkes RI No 028 Tahun 2011 tentang klinik, klinik dalam memberikan pelayanan berkewajiban menyelenggarakan rekam medis. Penyimpanan rekam medis yang baik menurut Dirjen Yanmed Tahun 2006 dengan cara melakukan penyortiran untuk mencegah kesalahan letak (missfile), serta menggunakan tracer sebagai petunjuk arah penyimpanan atau pengembalian rekam medis yang keluar dari rak penyimpanan, rekam medis yang missfile dapat diminimalisir dengan tracer. Tracer telah tersedia di Klinik Laras Hati, tetapi belum pernah dievaluasi penggunaannya. Mengetahui penggunaan tracer berkas rekam medis dan permasalahan penggunaan tracer di Klinik Laras Hati. Jenis penelitian adalah penelitian deskriptif kualitatif dengan pendekataan content analysis. Teknik pengumpulan data menggunakan wawancara mendalam, observasi, dan studi dokumentasi. Sampel dalam penelitian ini terdiri dari bidan, perawat, petugas registrasi dan petugas unit rekam medis di Klinik Laras Hati yang ditentukan dengan kriteria inklusi dan kriteria eksklusi. Penyimpanan rekam medis dengan system sentralisasi, nomor yang digunakan yaitu nomor rekam medis pasien. Sistem penjajaran dengan sistem SNF (Straight Numbering Filing). Adanya rekam medis yang ditempatkan dalam kardus berada di lantai, sehingga petugas kesulitan mencari dokumen rekam medis, dikarenakan rak penyimpanan kurang, penggunaan tracer kurang maksimal karena tidak semua petugas memanfaatkan tracer dalam pengambilan rekam medis, tracer juga belum diisi, jumlah tracer terbatas, sedangkan pasien yang berkunjung melebihi ketersediaan tracer. Kartu kendali pada tracer yang tidak terisi, sehingga tidak bisa untuk melacak tujuan berkas rekam medis, tidak adanya SOP penggunaan tracer